2011
DOI: 10.1021/pr2004743
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Proteome Analysis of Malignant Pleural Effusion for Lung Cancer Biomarker Discovery by Using Multidimensional Protein Identification Technology

Abstract: Malignant pleural effusion (MPE) obtained from lung adenocarcinoma may contain potentially useful biomarkers for detection of lung cancer. In this study, we used a removal system for high-abundance proteins followed by one-dimensional SDS-PAGE combined with nano-LC-MS/MS to generate a comprehensive MPE proteome data set with 482 nonredundant proteins. Next, we integrated the MPE proteome and secretome data sets from three adenocarcinoma cell lines, with a view to identifying potential PE biomarkers originating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 86 publications
1
47
0
1
Order By: Relevance
“…To filter out likely intracellular contaminants and retain proteins most likely to be secreted by live cells, we used the SignalP [26,27] and Gene Ontology (GO) [28,29] databases to retain only proteins either experimentally observed to be extracellular or otherwise containing predicted cleavable signal peptides targeting them to the secretory pathway. This analysis yielded a total of 298 unique, secretory-predicted proteins across the eight cell lines, which is in line with previous quantities and percentages of secreted proteins found in comparable secretome analyses [8,[30][31][32][33][34][35][36][37][38][39][40].…”
Section: Non-quantitative Bone Metastasis Secretome Analysissupporting
confidence: 84%
See 1 more Smart Citation
“…To filter out likely intracellular contaminants and retain proteins most likely to be secreted by live cells, we used the SignalP [26,27] and Gene Ontology (GO) [28,29] databases to retain only proteins either experimentally observed to be extracellular or otherwise containing predicted cleavable signal peptides targeting them to the secretory pathway. This analysis yielded a total of 298 unique, secretory-predicted proteins across the eight cell lines, which is in line with previous quantities and percentages of secreted proteins found in comparable secretome analyses [8,[30][31][32][33][34][35][36][37][38][39][40].…”
Section: Non-quantitative Bone Metastasis Secretome Analysissupporting
confidence: 84%
“…The first breast cancer metastasis secretome study profiled the secretomes of the MCF10A metastasis progression series, finding proteins such as alpha-1-antichymotrypsin and galectin-3-binding protein to be upregulated in conditioned media from the metastatic variants [48]. More recently, many secretome analyses of cell lines representing several different cancer types have been reported [8,[30][31][32][33][34][35][36][37][38][39][40]. Most secretome studies have used methodology similar to ours in terms of initial protein harvesting conditions and then have typically used either concentrating columns or total protein precipitation methods for secreted protein isolation.…”
Section: Mario Andres Blanco Et Al 1349mentioning
confidence: 99%
“…Therefore, application of multidimensional protein fractionation technology should be necessary to improve the number of identified PE proteins in the near future. The four proteins (AHSG, AGN, CST3, and IGFBP2) reported as the potential PE biomarkers in our previous NSCLC-MPE data set (9) were also identified/quantified in the current study (supplemental Tables S4 and S5). Consistent with our previous findings, the label-free quantification of these potential PE markers revealed that the protein levels in malignant PE were higher than the levels in nonmalignant PE (TB, PN, and PMPE), although the average ratio of NSCLC-MPE/PN for IGFBP2 was 0.97 (supplemental Table S19).…”
Section: Discussionmentioning
confidence: 78%
“…The entire gel lane was cut into 30 pieces and subjected to in-gel tryptic digestion as described previously (9). Briefly, gel pieces were destained in 50 mM NH 4 HCO 3 /ACN (3:2, v/v) three times for 25 min each and then dehydrated in ACN and dried in a SpeedVac.…”
Section: Patient Population and Clinical Specimens-this Study Was Appmentioning
confidence: 99%
See 1 more Smart Citation